2007
DOI: 10.1093/jxb/ern016
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of C4 photosynthetic enzymes in transgenic rice plants: an approach to introduce the C4-like photosynthetic pathway into rice

Abstract: Four enzymes, namely, the maize C(4)-specific phosphoenolpyruvate carboxylase (PEPC), the maize C(4)-specific pyruvate, orthophosphate dikinase (PPDK), the sorghum NADP-malate dehydrogenase (MDH), and the rice C(3)-specific NADP-malic enzyme (ME), were overproduced in the mesophyll cells of rice plants independently or in combination. Overproduction individually of PPDK, MDH or ME did not affect the rate of photosynthetic CO(2) assimilation, while in the case of PEPC it was slightly reduced. The reduction in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 37 publications
4
74
0
1
Order By: Relevance
“…For all three genes, the size of the mRNA indicates correct splicing in oat. In the case of PEPC and PPDK, this is consistent with previous work that indicated that full-length maize PEPC and PPDK genes driven by their native promoters are expressed and generate transcripts of the correct size in transgenic rice leaves (Ku et al, 1999;Fukayama et al, 2001;Taniguchi et al, 2008). The most parsimonious explanation is that the same transacting factors recognize maize PEPC and PPDK in these two C 3 grasses.…”
Section: Several Maize Transcripts Associated With C 4 Photosynthesissupporting
confidence: 88%
See 1 more Smart Citation
“…For all three genes, the size of the mRNA indicates correct splicing in oat. In the case of PEPC and PPDK, this is consistent with previous work that indicated that full-length maize PEPC and PPDK genes driven by their native promoters are expressed and generate transcripts of the correct size in transgenic rice leaves (Ku et al, 1999;Fukayama et al, 2001;Taniguchi et al, 2008). The most parsimonious explanation is that the same transacting factors recognize maize PEPC and PPDK in these two C 3 grasses.…”
Section: Several Maize Transcripts Associated With C 4 Photosynthesissupporting
confidence: 88%
“…Our finding that photosynthesis in the line containing chromosome 6 on which PPDK resides responded to both light and CO 2 supply in a similar way to controls is consistent with the fact that the expression of maize PPDK had no effect on net assimilation . It has been reported that expression of maize PEPC causes a slight reduction in net assimilation and stunting in transgenic rice plants (Taniguchi et al, 2008). Retarded growth that correlated with PEPC activity was also reported for potato (Solanum tuberosum; C 3 ) plants overexpressing a modified C 4 PEPC from Flaveria trinervia, and metabolite analysis of these plants revealed elevated levels of malate and total amino acids (Rademacher et al, 2002).…”
Section: Several Maize Transcripts Associated With C 4 Photosynthesismentioning
confidence: 71%
“…Enzyme activity measurements were performed on 48 strains, each with a different PPDK expression level, showing that there was only about a 20% change in the PEP formation rate despite a 5.7-fold variation in PPDK level. A similar phenomenon was also observed in transgenic rice (Oryza sativa) leaves, in which maize PPDKs accumulated at very high levels but failed to activate fully, even after 14 h of illumination and complete inactivation in darkness (Taniguchi et al, 2008). These findings suggest that the mechanism for regulating PPDK is far more complicated than previously thought.…”
supporting
confidence: 76%
“…The enzyme activities of PPDK and PEPC in these wheat lines were only about twofold and fourfold, respectively, higher than those of the control plants. These expression levels are much lower than those achieved in the transgenic rice plants (Ku et al 1999;Taniguchi et al 2008). Whether the differences in expression levels of these maize genes in the C 3 rice and wheat affect their photosynthetic performance and other physiological traits under different conditions remain to be investigated.…”
Section: Introductionmentioning
confidence: 93%
“…Later, the same construct was used to transform indica rice IR68899B using a bombardment method, and the transformants showed enhancement in photosynthesis rate under high temperature (Bandyopadhyay et al 2007). Now, it is generally agreed that overexpression of a single maize pepc gene encoding PEPC protein or even quadruple transformants overexpressing all four key enzymes in the C 4 photosynthetic pathway [i.e., PEPC, pyruvate, orthophosphate dikinase (PPDK), NADP-malate dehydrogenase (NADP-MDH), NADP-malic enzyme (NADP-ME)] into rice plants do not show dramatic improvements in photosynthesis under normal conditions (Taniguchi et al 2008;Kajala et al 2011;Miyao et al 2011). However, a recent study with transgenic wheat plants that overexpressed maize ppdk cDNA, maize pepc cDNA and both showed enhanced maximum daily photosynthetic rates of 4.5, 13.3 and 26.4%, respectively, and enhanced daily accumulated photosynthesis of 6.9, 13.9 and 21.3%, respectively, as compared with the wild-type plants (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%